Penyuluham Hukum Dampak Penggunaan Gadget Secara Berlebihan Bagi Anak Usia Sekolah Dasar di SDN Sidodadi 2 Sidoarjo - Bambang S. Irianto; Zenita Delia Reviska; Khamilatun Nisah; Amelia Suci Ramadhani; Joshua Aldo Tri Putra (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
In this era of digitalization, almost all Indonesian people use gadgets. This also seems to have become an inseparable phenomenon in this era of digitalization, especially among young people in Indonesia, including elementary school children. The impact of using the gadget itself also varies, ranging from the positive impact that can be taken and the negative impact that must be avoided. Lack of knowledge about the impact of gadget use for elementary school children, students of the Faculty of Law UPN Veteran East Java conducted socialization at SDN Sidodadi 2. The target of this socialization activity is 5th grade elementary school children with a total of 55 students. This socialization activity aims to provide understanding and legal knowledge about the impact of excessive use of gadgets, especially since 5th grade elementary school children are the age when the transition from children to the adolescent phase is born. This socialization activity uses a special approach method so that in the delivery process it can be well received and on target. The results of socialization activities are summarized into reports and journals so that benefits and learning can reach the wider community.